A rare presentation of supraclavicular schwannoma - Waseem, Shaik Mohammed; Subbarayappa, Srinath; Nagaraja, Jayanth Bannur (Indian Journal of Case Reports, 2020)
Schwannomas or neurilemmomas are benign tumors that arise from Schwann cells that surround the peripheral, cranial, or autonomicnerve sheaths. These are slow-growing, benign, encapsulated tumors that arise from the proliferating Schwann cells, encompassing the nerve sheath. About 25–45% of the schwannomas are found in the head-and-neck region. These tumors can arise from any of the cranial, peripheral, or autonomic nerves and constitute